Efficacy and Side Effects of Drugs Commonly Used for the Treatment of Lower Urinary Tract Symptoms Associated With Benign Prostatic Hyperplasia - Yu, Zhao-Jun; Yan, Hai-Lan; Xu, Fang-Hua; Chao, Hai-Chao; Deng, Lei-Hong; Xu, Xiang-Da; Huang, Jian-Biao; Zeng, Tao (Frontiers in Pharmacology, 2020)
Benign prostatic hyperplasia (BPH) is the most common benign disease of the prostate gland, and is caused by benign hyperplasia of the smooth muscle cells and stromal cells in this important gland. BPH is also the most common disease underlying lower urinary tract symptoms (LUTS). The incidence of BPH increases with age and affects more than half of all men aged 50 years or older. BPH mainly exerts effects on urinary function and can seriously reduce a patient's quality of life. At present, treatment for BPH aims primarily to improve the quality of life and reduce the risk of BPH-related complications. Pharmacological therapy is recommended for moderate-to-severe cases of LUTS that are suggestive of BPH. A range of drugs is currently available to treat this condition, including α1-adrenoceptor antagonists, 5α-reductase inhibitors (5-ARIs), phosphodiesterase type 5 inhibitors (PDE5Is), muscarinic receptor antagonists (MRAs), β3-adrenoceptor agonists, and plant extracts. Of these, the most commonly used drugs in the clinic are α1-adrenoceptor antagonists, 5-ARIs, and combination therapy. However, these drugs exert their effects via various mechanisms and are associated with adverse reactions. The purpose of this review is to provide current comprehensive perspectives on the mechanisms of action, efficacy, and adverse reactions associated with the drugs most commonly used for the treatment of BPH.